Career trajectory of Major League Baseball draftees with a history of spondylolysis or lumbar disc herniation - Epner, E.; Hedt, C.; Jack II, R. A.; Lambert, B.; McCulloch, P. C.; Lintner, D. M. (Sport-Orthopädie - Sport-Traumatologie, 2022)
Summary Objective Lumbar spondylolysis (SPONDY) and lumbar disc herniation (DISC) are common lumbar spine injuries that occur in baseball athletes. The purpose of this study was to determine whether Major League Baseball (MLB) draftees with a history of SPONDY or DISC have shorter career length, lower level of professional advancement, and longer cumulative time on the injured list than healthy controls.